Risk factors for KPC‐producingKlebsiella pneumoniae: watch out for surgery. Issue 6 (June 2016) - da Silva, Kesia Esther; Maciel, Wirlaine Glauce; Sacchi, Flávia Patussi Correia; Carvalhaes, Cecilia Godoy; Rodrigues‐Costa, Fernanda; da Silva, Ana Carolina Ramos; Croda, Mariana Garcia; Negrão, Fábio Juliano; Croda, Julio; Gales, Ana Cristina; Simionatto, Simone
Abstract : N/A: This study describes the molecular characteristics and risk factors associated with carbapenem‐resistant Klebsiella pneumoniae strains. Risk factors associated with KPC‐producing K. pneumoniae strains were investigated in this case‐control study from May 2011 to May 2013. Bacterial identification was performed by matrix‐assisted laser desorption/ionization‐time‐of‐flight mass spectrometry (MALDI‐TOF MS). Antimicrobial susceptibility was determined by broth microdilution. Carbapenemase production was assessed by both modified Hodge test (MHT) and ertapenem hydrolysis using MALDI‐TOF MS. The presence of β ‐lactamase‐encoding genes was evaluated by PCR and DNA sequencing. Alterations in genes encoding K. pneumoniae outer membrane proteins were analysed by PCR and DNA sequencing as well as SDS‐PAGE. Genetic relatedness among strains was determined by pulsed‐field gel electrophoresis. This study included 94 patients. Longer hospitalisation, mechanical ventilation, catheters, and previous surgery were associated with KPC‐producing K. pneumoniae . Sixty‐eight strains showed resistance to carbapenems. Carbapenemase production was detected by MHT in 67 K. pneumoniae strains and by MALDI‐TOF MS in 57. The presence of the bla KPC‐2 gene was identified in 57 strains. The bla KPC‐2 gene was not found in 11 carbapenem‐resistant K. pneumoniae ; instead, the bla CTX‐M‐1‐like, bla CTX‐M‐2‐like, bla CTX‐M‐8 like, bla CTX‐M‐14‐like and bla SHV‐ like genes associated with OmpK35 and OmpK36 alterations were observed. Thirty‐three KPC‐producing K. pneumoniae strains were clonally related, and patients infected with these strains had a higher mortality rate (78.78 %). Our results show that KPC‐producing K. pneumoniae was associated with several healthcare‐related risk factors, including recent surgery.